PERANCANGAN SISTEM INFORMASI INDEKS ALAMAT PASIEN RAWAT JALAN DI RUMAH SAKIT BHAYANGKARA KOTA BENGKULUPERANCANGAN SISTEM INFORMASI INDEKS ALAMAT PASIEN RAWAT JALAN DI RUMAH SAKIT BHAYANGKARA KOTA BENGKULU - Aulia Moura Yutisya; Khoirun Nisa Nahda Hanifah (Jurnal Infokes, 2021)
This research aims to design and build information system of index address an outpatient using Microsoft Visual Studio 2010 in Rumah Sakit Bhayangkara Bengkulu. The data were collected from doing an internship, observing, interviewing, and library study. The research method used is waterfall method with Data Flow Diagram as software program. The programming language used Microsoft Access 2010, and the software testing used Blackbox method. There some problems of this research (1) There is no system of information like program or application index address outpatient. (2) The report processing of index address outpatient still uses Microsoft Excel which causes less effective, lot of mistakes, and takes a long time to be recorded. There are some suggestions which the author gave; (1) It is needed to design and build the information system of index address outpatient so that the data processing will be effective and efficient. (2) The software or specific application needs to be built so that the processing of data will not take long time. Keywords: Designing, System Information, Index Address Outpatient, Medical Record, Microsoft Visual Studio 2010.